(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Forensic Medicine, Forensic Science, and Toxicology have advanced significantly over the last few decades worldwide. Quality management in the context of forensic and analytical fields is an important aspect from the perspective of a state and the country for proper and timely disbursement of Justice. Forensic evidence analysis can affect the victim or accused’s life significantly. It can lead to criminal trials or civil trials, acceptance or denial of compensation, loss of job, loss of career, loss of health, children in custody, and others1,2,3. The quality of the forensic evidence shall meet or exceed the legal requirements as well as the scientific expectations in the court of law. On the other hand, it must be agreeable and flexible to the police, doctors, forensic experts, and forensic scientists for handling different body tissues and other articles related to a medicolegal case. After collection of the evidence and preservation of that maintaining the chain of custody, it is sent to the Forensic Science Laboratories for testing and report preparation. These reports are produced before the court of law as evidence to establish the facts scientifically. The documentation of activities and testimony based upon scientific facts plays a vital role in criminal justice system of any country.